Assessment of Power System Equipment to Enhance the Power Quality at Dr. Saiful Anwar General Hospital Malang - Reza Sarwo Widagdo; Puji Slamet; Aris Heri Andriawan; Balok Hariadi; Izzah Aula Wardah; Elvianto Dwi Hartono (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Electrical conditions in the operations building and substation of the regional general hospital Dr. Saiful Anwarexperienced a power cut at optimum load, resulting in the power supply being solely obtained from the generator. The aim of the assessment carried out was to delve deeper into power quality, electrical performance, and other supporting equipment to maximize service to patients based on the assessment findings. The assessment stages utilized were the initial assessment stage and the detailed assessment stage. The analysis stages were conducted under steady-state load conditions. The assessment process involved field measurements, observations, and interviews with technical staff at the general hospital Dr. Saiful Anwar. Field measurements utilized Ammeters, Voltmeters, and Harmonic Analyzers to ascertain voltage imbalances, current imbalances, and harmonic content in SDP panels on each floor of the operations building, as well as to evaluate UPS components as backup power and stabilizers for electrical equipment. The results of observations and direct measurements in the field revealed several issues, including a current harmonic content of up to 50% on the 6th floor of the operations building (OK6) and in the Linac room, along with various other findings related to voltage and current imbalances in the secondary substation and certain components. The UPS, alike to the battery and filter capacitor inside, requires replacement. Additionally, regarding the grounding value, which currently stands at 3 Ohms, it is imperative to incorporate a parallel grounding system to bring the value below 1 Ohm to mitigate the risk of leakage current occurrences.